1997
DOI: 10.1046/j.1471-4159.1997.68020739.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Cathepsins E and D in Neurons of the Aged Rat Brain and Their Colocalization with Lipofuscin and Carboxy‐Terminal Fragments of Alzheimer Amyloid Precursor Protein

Abstract: Age‐related changes in the expression and localization of two distinct intracellular aspartic proteinases, cathepsin E (CE) and cathepsin D (CD), were investigated in the rat cerebral cortex and the brainstem by immunocytochemical and quantitative methods using discriminative antibodies specific for each enzyme. Non‐lysosomal CE was barely detectable in these two brain tissues in the embryonic stages, whereas relatively high expression of lysosomal CD was observed in embryonic tissues. After birth, CE was incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 45 publications
5
57
0
Order By: Relevance
“…Several studies suggest that CD participates in the signaling pathways leading to cell death. In addition, CD levels are significantly increased during the normal aging process (48). Here, CD was dramatically increased during senescence and decreased during apoptosis.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies suggest that CD participates in the signaling pathways leading to cell death. In addition, CD levels are significantly increased during the normal aging process (48). Here, CD was dramatically increased during senescence and decreased during apoptosis.…”
Section: Discussionmentioning
confidence: 89%
“…However, whether the impairment of cathepsin Dmediated apoptotic pathways contributes somehow to the development of both the gastrointestinal and the neuronal pathologic phenotypes is not known, although it seems rather unlikely. Indeed, cathepsin D has been found to play an important role in various pathological conditions, the majority of which affects the CNS, where its contribution seems to be limited to alterations of normal proteolytic processes rather than induction of cell death (Banay-Schwartz et al, 1987;Matus and Green, 1987;Nakanishi et al, 1997). Nonetheless, studies employing cathepsin D-deficient cells, as well as specific pharmacological inhibitors, have demonstrated that cathepsin D is a central mediator of apoptosis induced by several stimuli, such as staurosporine, death receptor-activation, growth factor-deprivation, and oxidative stress (Roberg and Ollinger, 1998;Brunk and Svensson, 1999;Kagedal et al, 2001a;Johansson et al, 2003).…”
Section: Mechanisms Of Lysosome-mediated Apoptosismentioning
confidence: 99%
“…Electrophoresis and Immunoblotting-Detailed electrophoresis and immunoblotting procedures were described previously (41,42). Briefly, cells in dishes were washed with phosphate-buffered saline and mechanically removed.…”
Section: Generation Of Ova-(266 -281)-specific I-a B Restrictedmentioning
confidence: 99%